Peningkatan Pemahaman Bacaan Mahasiswa melalui Teknik Think-Pair-Share Berbasis Lesson Study - Made Aryawan Adijaya (ACARYA PUSTAKA, 2017)
AbstractThis research aims at improving the reading text comprehension of D3 English department of Ganesha University students through think, pair and share technique with lesson study basis, and finding out the students’ response towards the implemented technique.   It employes the teaching system development method with lesson study model by Lewis (2002). The research was done within 3 cycles due to limitation of time. Each cycle consists of 3 activities such as: 1) plan,  2) do, 3) see. The subjects were 12 students of D3 English department of Ganesha University  at 4th semester who took Reading 3 course. The data were gathered through observation, and evaluation taken from reading comprehension tests. The analysed data show that the students were very happy with the implemented technique, and felt motivated in doing all phases of learning. The improvement of students’ reading comprehension was known by comparing the score of all meetings. The main scores improved from 65.83 at the 1st cycle to 75.83 at the 2nd cycle and to 83.75 at the 3rd cycle. Key words : reading comprehension, think-pair-share, lesson study